STRUCTURING PRODUCT VALUE CREATION AND DELIVERY PROCESSES TO DEVELOP QUALITY BUSINESS RELATIONSHIPS. Case study of metal processing machinery company from Finland - Kreposna, Mariia (My University, 2015)
Purpose – in the era of common application of relationship marketing as a strategy to succeed in business-to-business markets, there is a tendency to neglect the proper management of business relationships and as a result – discontent with the prevailing cooperation routines. Thus, this paper is aimed on developing guiding principles to create and maintain successful buyer-seller relationships. Design/methodology/approach – the paper is built upon linear-analytical structure with minor application of systemic combining approach in corresponding empirical findings to theoretical knowledge. Since qualitative data, collected through embedded single- and multiple-cases, embraces a comprehensive study of the product value phenomenon, methodology is concentrated on finding links between variables to reveal the control arms of business relationships. That is why data is interpreted in form of logic model based on within- and cross-case analysis. Findings – A pledge of quality relationships lies in keeping constant contact between buyers and sellers through formal and informal communications, provision of sufficient service support as well as cooperation resulting in trust, commitment and satisfaction. Research limitations/implications – the paper is limited in several dimension. First – the study takes place in clearly outlined time frames. Second – the research design limits methodological approaches to only corresponding tools. Finally, data collection sample is limited in number – 3 customer companies and geography – customer companies represent Finnish and Danish markets. Originality/value – although the unit of analysis - business relationships, is a broad concept that may lead to fuzzy results, it has been studied as a phenomenon, with emphasis on causal relationships between the elements. This opens clear perspectives on what they consist of, how they emerge and develop, what activities are involved and most important – how to manage the relationships in a desired way.
Keywords: business relationships; product value; value drivers; quality of business relationships; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in Strategic Management|